MENGUPAS TATA KELOLA PERIKANAN NASIONAL MELALUI PP NO. 11 TAHUN 2023 TENTANG PENANGKAPAN IKAN TERUKUR DEMI MEWUJUDKAN BLUE ECONOMY - Luthfia, Sahira Sajjadia (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2023)
Fisheries governance plays a major role in national welfare. As an archipelagic country, Indonesia needs to pay great attention to the sustainability of national fisheries. This article aims to explore the fidelity of the Blue Economy from a legal perspective as a marine economic order that provides economic and social benefits while taking into account environmental sustainability. The juridical review focused on Government Regulation Numb.11 of 2023 on Measured Fishing and its compatibility with the transformation towards a Blue Economy in Indonesia. The author uses a sociological-empirical (non-doctrinal) approach that sees law as a social institution that is always related to social variables. It was found that most of the articles in this regulation have fulfilled the elements of Blue Economy. However, there are still legal loopholes such as the lack of clarity in the definition of small fishermen who are excluded in some provisions, determination of WPPNRI areas that tend to be exploitative, and inequality in port facilities. With wise and sustainable measures, Indonesia can optimize its potential as an archipelago with huge fisheries potential to realize a Blue Economy that provides social, economic, and environmental benefits for current and future generations.Keyword: National fisheries governance, Â PP numb. 11 of 2023, Measured Fishing, Blue Economy.